Development of heat tolerant strawberry (Fragaria x ananassa dush., cv. camarosa) plants through Agrobacterium-mediated transformation - Haddadi, Fatemeh (2012)
In Malaysia strawberry production is limited to the highland areas. Hence, based on the limitation of production areas the application of genetic engineering to produce a heat tolerant strawberry may facilitate the cultivation of the crop on the lowland areas. An Agrobacterium-mediated transformation method was applied to introduce the AtHSP101 cDNA into strawberry cv. Camarosa. The AtHSP101 cDNA under the control of CaMV35S promoter was cloned into the multiple cloning sites of pGreen0049. The construct was named pGFHSP and successfully introduced into Agrobacterium LBA4404. In vitro regeneration system from strawberry leaves used in the transformation was optimized by the application of different thidiazuron (TDZ) concentrations in MS medium. TDZ at 16 μM showed the highest percentage (100 %) of shoot formation and the highest mean number of shoots (24) produced per explant. Effect of different antibiotics (timentin, cefotaxime, carbenicillin and ampicillin) on shoot regeneration of strawberry leaf explants showed the best shoot regeneration in the presence of 300 mg/l timentin and 150 mg/l cefotaxime. Determination of the minimum inhibitory concentration (MIC) of kanamycin was carried out using leaf explant for effective screening of strawberry putative transformants. Kanamycin at 50 mg/l, with shoot regeneration percentage of 0 % and mean number of 0 shoot per explant was selected as the MIC. Assessment of different factors affecting Agrobacterium mediated-transformation of strawberry with the AtHSP101 showed the highest efficiency of putative transformant production (83 %) in treatment with no preculture, bacterial OD600 of 0.6 and the addition of 150 mg/l cefotaxime in the pre-selection and selection media. The presence of the AtHSP101 in the plant genome was verified by luciferase reporter gene assay. Nested PCR amplification of genomic DNA isolated from each putative transformed plantlet showed the expected 520 and 689 bp products of AtHSP101 and CaMV35S promoter primers, respectively. Southern blot analysis of the transgenic strawberry showed the presence of one, two and three copies of the transgene in the plant genome. Analysis of the AtHSP101 expression at the mRNA level by RT-PCR showed the expected band of 520 bp corresponding to the AtHSP101 cDNA. Protein dot blot and western blot analysis of the transgenic lines with one copy number of the transgene indicated the positive interaction of protein with the antibodies confirming the expression of AtHSP101 at the protein level. DNA dot-blot analysis of the transgenic strawberry lines derived from runners and having one copy number of the transgene showed the presence of a hybridization sequence homologous to the AtHSP101. Greenhouse evaluation of the transgenic strawberry lines exhibited robust growth and performance compared to the non-transgenic control plant. Study on the effect of two temperatures, 20 and 30 °C showed greater growth and productivity in the transgenic lines compared to the control plants. Analysis of transgenic strawberry plants exposed to heat shock, gradual heat and drought stresses showed significant differences in their morphological characters and AtHSP101 protein level, measured by ELISA, compared to the control plants. The results of this study indicated that the expression of the AtHSP101 may have an application to protect the transgenic strawberry plant under high temperature and drought conditions.